(untitled) (Global Journal of Medical Research, 2021)
Purtscher s retinopathy was described by German Ophthalmologist Otmar Purtscher in 1910 It is an occlusive microvascular retinopathy caused by trauma such as head injury thoracic compressive injury or long bone fractures 1 Without history of trauma it can also be due to systemic disease like acute pancreatitis renal failure lymphoproliferative disorder valsalva maneuver fat embolism syndrome or autoimmune diseases and they present with similar retinal findings and it is called Purtscher like retinopathy 2 Patients usually come with reduced visual acuity following injury Clinical findings commonly seen in retina include cotton wool spots retinal haemorrhage areas of retina whitening Purtscher flecken or optic disc oedema And 60 of cases have bilateral involvement 3 Purtscher flecken pathognomonic of Purtscher s retinopathy are typically seen in posterior pole sparing the perivascular areas 4 5